-2k-5=-k+3

Simple and best practice solution for -2k-5=-k+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2k-5=-k+3 equation:


Simplifying
-2k + -5 = -1k + 3

Reorder the terms:
-5 + -2k = -1k + 3

Reorder the terms:
-5 + -2k = 3 + -1k

Solving
-5 + -2k = 3 + -1k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add 'k' to each side of the equation.
-5 + -2k + k = 3 + -1k + k

Combine like terms: -2k + k = -1k
-5 + -1k = 3 + -1k + k

Combine like terms: -1k + k = 0
-5 + -1k = 3 + 0
-5 + -1k = 3

Add '5' to each side of the equation.
-5 + 5 + -1k = 3 + 5

Combine like terms: -5 + 5 = 0
0 + -1k = 3 + 5
-1k = 3 + 5

Combine like terms: 3 + 5 = 8
-1k = 8

Divide each side by '-1'.
k = -8

Simplifying
k = -8

See similar equations:

| m-9m-8m-5= | | 1+x=x-5 | | 2x+6x+8=36 | | -3(m-8)=3 | | P=22p | | 225-6x=30x+21 | | -3m+16=32-7m | | 2+5x=42 | | 3f+2=4f+4 | | 60(12+2.5m)=1 | | 20k+100=10k+120 | | 4x+5(5+x)=-2 | | 2-x=5x+14 | | 6(-m-8)+4(6m+4)=2m+13-4m | | 4y+3-3y=6 | | 3r^2+2r-3=0 | | 5n+1/8=3n-5/4 | | -7x-5=-33 | | -1(3-10y)=12 | | 5p-7=2p-4 | | 4g+6=2g+14 | | 4x^2+16x-15=0 | | t+(-14)= | | 7-4*x=13 | | -4y+7=-21 | | 3b-4=5b-2 | | 9-5n=30 | | 4(b-2)=2(b-6) | | 7x-(4x-6)=30 | | 6r-(-2r-27)=21 | | 19-4c= | | 18=10+4x+4 |

Equations solver categories